THE FEASIBLE MARKETING STRATEGY FOR CATSWOPPR IN THE NETHERLANDS - M Naufa Adifyanto N.P; Ismi Darmastuti; Aulia Vidya Almadana (Diponegoro Journal of Management, 2023)
ABSTRACT This research aims to determine a feasible strategy to increase brand and target market awareness as well as produce an appropriate and effective marketing strategy through social media to help launch their first service in the Netherlands. This strategy is expected to increase brand awareness and increase CatSwoppr's social media traffic. To produce an appropriate and effective strategy, complete and comprehensive information is required. This strategy is expected to increase brand awareness and increase CatSwoppr's social media traffic. To produce an appropriate and effective strategy, complete and comprehensive information is required. The author also collects research results and journals from various previously available sources, which include cats in Europe and social media in the Netherlands. Based on the results of the analysis, most of CatSwoppr's audience or target market is currently in the Netherlands, especially those in Amsterdam, Utrecht, Haarlem, Rotterdam, and The Hague with an average age between 25-34 years, followed by various other European countries and countries in Asia. In addition, this research also produces marketing strategies that are expected to be effective by trying to communicate with the target market through social media andwebsites. In the recommendations section, the author also describes the strategies and stepsthat must be taken by CatSwoppr to maximize the use of social media and websites as platforms for marketing